Sex/gender-related differences in inflammaging. (April 2023) - Olivieri, Fabiola; Marchegiani, Francesca; Matacchione, Giulia; Giuliani, Angelica; Ramini, Deborah; Fazioli, Francesca; Sabbatinelli, Jacopo; Bonafè, Massimiliano
Abstract: Geroscience puts mechanisms of aging as a driver of the most common age-related diseases and dysfunctions. Under this perspective, addressing the basic mechanisms of aging will produce a better understanding than addressing each disease pathophysiology individually. Worldwide, despite greater functional impairment, life expectancy is higher in women than in men. Gender differences in the prevalence of multimorbidity lead mandatory to the understanding of the mechanisms underlying gender-related differences in multimorbidity patterns and disability-free life expectancy. Extensive literature suggested that inflammaging is at the crossroad of aging and age-related diseases. In this review, we highlight the main evidence on sex/gender differences in the mechanisms that foster inflammaging, i.e. the age-dependent triggering of innate immunity, modifications of adaptive immunity, and accrual of senescent cells, underpinning some biomarkers of inflammaging that show sex-related differences. In the framework of the "gender medicine perspective", we will also discuss how sex/gender differences in inflammaging can affect sex differences in COVID-19 severe outcomes. Highlights: ● Inflammaging is at the crossroad of aging and age-related diseases. ● Sex-related differences exist in the age-dependent accrual of senescent cells and remodeling of innate and adaptive immunity. ● The most extensively investigated biomarkers of inflammaging show sex-related differences. ● Sex-related differences in immunological responses and inflammaging rate could affect COVID-19 outcomes.